Prevalencia de virus influenza a y b mediante RT-qPCR en Piura, Perú marzo – diciembre 2018 - Guerrero Seminario, Eissen Emerson (2019)
In order to determine the prevalence, seasonality and subtypes of Influenza A and B in the Piura Region during 2018, a descriptive observational cross-sectional study was developed, using the real-time polymerase chain reaction technique RT-qPCR. 96 nasopharyngeal swab samples were processed taken and derived to Laboratorio de Salud Pública Piura, A prevalence of 18.8% (95% CI 12.2% - 27.7%) was obtained; being 14.6% for InfluenzaA and 4.2% for Influenza B. The age group with the highest prevalence were young adults between 5 - 44 years old with 71.4% positive cases for influenza A and 15 – 44 years with 50% for influenza B. The male gender, mild predominance was observed, although without significant statistical difference. The associated symptomatology was cough 77.8%, fever 66.7%, respiratory difficulty 33.3% and the seasonal pattern of circulation occurred in the fall-winter season with 94% of cases, coinciding with similar studies. Influenza being a disease of importance in public health had as the main etiological agent by subtyping H1N1 pdm09 with 85.7% of influenza A, so it is of great importance to continue research on this pathology.